The Relationship of The Level of Family Knowledge With Compliance With Medication In Glaucoma Clients At Poli Rumah Eye Undaan Surabaya - Jajuk Winarni; Achmad Parjiko Adji Sanjaya; M. Khoirudin (Kirana Publisher (KNPub), 2022)
Glaucoma is the second largest cause of blindness after cataract. Blindness due to glaucoma is irreversible. However, blindness in patiens due to glaucoma can be prevented by increasing patient compliance in drug use. This research was using an observational analytic study with a cross-sectional study approach. The research respondents were 50 glaucoma patients who were undergoing treatment and fulfilling the inclution criteria at Eye Hospital of Undaan Surabaya. Data collected in this study are primary data. Data was collected by interviewing with a closed questionnaire guide. Statistical tests performed were validity, realibily, and spearman correlation tests. Result A significant relathionship was optained between knowledge and adherence to treatment (p=0,000). Strong statitiscal relathionship of 0.728 range of values berween variables including the strong category (0,6 – 0,8), and the direction of correlation is positive which means the higher the level of knowledge, the impact on the higher level of treatment adherence.